Safety evaluation of baloxavir marboxil: analysis and discussion utilizing real adverse events from the FAERS database - Xiaolong Lai; Liuyin Jin; Yixia Zhou; Yang Li; Lindan Sheng; Guomin Xie; Jianjiang Fang (BMC Pharmacology and Toxicology)
Abstract Background As a novel anti-influenza agent, baloxavir marboxil lacks real-world safety data in large populations. Therefore, this study aimed to investigate adverse drug events (ADEs) associated with baloxavir marboxil by analyzing the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods Adverse event reports involving baloxavir marboxil were extracted from the FAERS database spanning the fourth quarter of 2018 to the third quarter of 2023. Demographic characteristics and reporter profiles were analyzed to characterize the exposed population. A disproportionality analysis was performed using four validated pharmacovigilance algorithms: reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and multi-item gamma Poisson shrinker (MGPS). These complementary approaches were employed to detect, prioritize, and validate potential safety signals. Results Analysis of 8,824,675 ADE reports from the FAERS database identified 1,654 cases (0.19%) associated with baloxavir marboxil. Pediatric patients (< 18 years) exhibited the highest ADE reporting rate. Geospatial analysis revealed marked clustering, with 98.97% of reports originating from the United States (63.2%) and Japan (35.77%). We detected 47 significant safety signals spanning 27 System Organ Classes (SOCs), including established reactions such as pneumonia (n = 90) and vomiting (n = 77). Novel signals emerging from the analysis comprised hemorrhagic diathesis (n = 3), rhabdomyolysis (n = 25), hepatic dysfunction (n = 13), and cardiorespiratory arrest (n = 7). Notably, bleeding-related events (e.g., ischemic colitis, IC025 = 5.03) and neurological complications (e.g., febrile delirium, IC025 = 9.12) demonstrated statistically significant associations. Conclusion This pharmacovigilance study identifies previously undercharacterized safety signals associated with baloxavir marboxil, including hemorrhagic complications, liver dysfunction, rhabdomyolysis, and life-threatening cardiorespiratory events. Pediatric populations and patients on anticoagulants may require heightened monitoring. While these findings provide critical pharmacovigilance insights, our study is inherently constrained by the spontaneous reporting system, which introduces potential underreporting, reporting biases, and confounding factors. Future research could employ more rigorous prospective study designs, integrating clinical trials and epidemiological studies, to more accurately assess the safety risks of baloxavir marboxil.